Seed credit model in Uganda: Participation and empowerment dynamics among smallholder women and men farmers - Nanyonjo, Grace; Nchanji, Eileen (Elsevier, 2023)
Seed is life and can be a source of empowerment and disempowerment for women and men farmers. In this study, to close the gender gaps in seed, the Community Enterprises Development Organization, the Alliance of Bioversity and CIAT and the National Agricultural Research Organization developed a seed credit model available to men and women belonging to farmer groups. A mixed method was used to collect information from two districts in central Uganda on how the seed credit model reconstructed access, use, control and resulting benefits. Results showed that the provision of the seed credit model was considered a blessing even though it had many nuances. As a result of the seed credit model, we saw increased productivity in women's fields, increased income and decision making over income incurred from the sale of their crops. Their social status has been enhanced, and they now occupy a place of respect in their communities and households, where they can make decisions and get assets like houses and land. While it increased productivity, income and enhanced food and nutrition security needs of the family, it also changed power dynamics within the household as women become more empowered. To maintain power relations, men limited women's access to fertile land and family labor, which defined the quantity of seed gotten from the seed credit model. Women's participation and involvement in the seed credit model decreased over time as they were expected to pay their spouses' seed loans. Men's participation decreased because they were no longer entrusted with seed loans as their payment rate was very low. As we reap positive benefits, we have to ensure we don't ‘do harm’ when empowering our beneficiaries.